Blend de óleo essencial em dieta de bovinos confinados sem forragem - Mota, Lucas Gimenes (2022)
The objective of this study was to evaluate the effects of an essential oil blend (EO), based on cinnamaldehyde and diallyl disulfide, associated or not with monensin on consumption and digestibility, ingestive behavior, rumen fermentation, nitrogen metabolism, and blood metabolites of feedlot cattle feeding a no-forage diet. The experimental design was in a 5×5 latin square. The experimental diet was formulated using ground corn (82%), cotton cake (15%), mineral premix (3%), and the tested additives. The treatments consisted of a blend of essential oil, monensin and virginiamycin, combined and separately: CON (monensin 30 mg/kg DM), VM (25 mg/kg DM virginiamycin and 30 mg/kg DM monensin), MOE25 (30 mg/kg DM of monensin and 25 mg/kg DM of essential oil), MOE35 (30 mg/kg DM of monensin and 35 mg/kg DM of essential oil) and OE35 (35 mg/kg DM of essential oil). There was no effect of additives and their combinations on the intake and apparent digestibility of nutrients, except for the apparent digestibility of crude protein, with a contrast between the VM treatment and the treatments containing EO. The treatments did not influence the variables of ingestive behavior. There was no effect of treatments on ruminal pH and N-NH3. The time in which the pH remained below 5.8 and 5.6 was similar between treatments. There was a contrasting trend in the minimum pH between the VM treatments and with the addition of EO. There was no difference between treatments in ruminal microbial protein synthesis. Blood glucose concentration was higher 4 hours after morning feeding in all treatments. There was a difference in contrast between the MV treatments and the addition of EO for the concentration of D-Lactate and L-Lactate in the blood, in which a higher concentration of D-Lactate and L-Lactate in the blood was observed in the VM treatment than those that had EO. There was no difference between the additives in the concentration of cortisol metabolites in the feces. The blend of essential oil studied, containing cinnamaldehyde and diallyl disulfide, associated or not with monensin, does not change the nutritional parameters and metabolism of feedlot cattle feeding a no-forage diet.